Potent High-Affinity Antibodies for Treatment and Prophylaxis of Respiratory Syncytial Virus Derived from B Cells of Infected Patients - Collarini, Ellen J; Lee, F. Eun-Hyung; Foord, Orit; Park, Minha; Sperinde, Gizette; Wu, Hai; Harriman, William D; Carroll, Stephen F; Ellsworth, Stote L; Anderson, Larry J; Tripp, Ralph A; Walsh, Edward E; et al. (The Journal of immunology (1950), 2009)
Native human Abs represent attractive drug candidates; however, the low frequency of B cells expressing high-quality Abs has posed a barrier to discovery. Using a novel single-cell phenotyping technology, we have overcome this barrier to discover human Abs targeting the conserved but poorly immunogenic central motif of respiratory syncytial virus (RSV) G protein. For the entire cohort of 24 subjects with recent RSV infection, B cells producing Abs meeting these stringent specificity criteria were rare, <10 per million. Several of the newly cloned Abs bind to the RSV G protein central conserved motif with very high affinity (Kd 1–24 pM). Two of the Abs were characterized in detail and compared with palivizumab, a humanized mAb against the RSV F protein. Relative to palivizumab, the anti-G Abs showed improved viral neutralization potency in vitro and enhanced reduction of infectious virus in a prophylaxis mouse model. Furthermore, in a mouse model for postinfection treatment, both anti-G Abs were significantly more effective than palivizumab at reducing viral load. The combination of activity in mouse models for both prophylaxis and treatment makes these high-affinity human-derived Abs promising candidates for human clinical testing.